Adventures in natural product chemistry - Ward, Thomas E (2020)
Halichlorine, pinnaic acid and pinnarine are a novel family of marine alkaloids, characterised by their common 6-aza-spiro[4.5]decane ring system. First isolated in 1996 by Uemura et al, they have been shown to be biologically active with potential applications in the fields of inflammatory response and tumor metastasis.